The potential of involving sea transport in the reverse supply chain of used textiles - Shaheen, Danial; Strand, Carl (My University, 2022)
Today’s linear material flows account for half of society’s climate effect due to the increasing rate of products being produced and discarded. To address this issue, the concept of circular economy (CE) has become a trend in recent years and aims towards keeping the products in the economy for as long as possible. Textiles is one material which have received increased attention from the European Union due to the potential of having an increased circularity of the material. Furthermore, Sweden, which is a member state of the European Union, has the aim of increasing the circularity in the economy through a new strategy that specifically targets the textile industry due to the loss of resources this industry characterizes. Several Non- governmental organizations (NGOs) in Sweden contribute to CE initiatives by collecting used textiles from consumers which otherwise have a high probability to end up in household waste and eventually sent for incineration. The NGOs aim to sell the collected textiles in their secondhand stores but due to the limited domestic demand for used textiles, the majority are exported. However, the vast amount of transportation needed to export the used textiles can be perceived as an environmental trade-off due to the emission of greenhouse gases, especially if the transport is conducted by road. Sea as a mode of transport entails many economic and environmental benefits as opposed to road transportation. In addition, limited research considering modal choice in the reverse supply chain of used textiles in Sweden has been conducted which is a literature gap this thesis aims to close. Thus, the thesis comprises a qualitative approach to identify the potential for involving sea transport to a higher extent in the export of used textiles. During this study, several actors including NGOs, ports, and industry experts were interviewed with the aim of identifying barriers and drivers for involving sea transport to a higher extent in the reverse supply chain of used textiles. High costs, laws and regulations, and existing and efficient reverse flow were some of the main barriers identified. Reduced emissions, including external cost in total transportation costs and future recycling centers in Sweden were found to be the main drivers. Eventually, the more dominant barriers opposed to drivers were synthesized to draw conclusions on how to overcome the barriers and accentuate the drivers. The most essential recommendations constituted of including external costs in the total transportation cost, increasing the communication between the actors and overseeing the current highly efficient reverse flow of used textiles.